2012
DOI: 10.1073/pnas.1219028109
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of CREB recognition and coactivation by the CREB-regulated transcriptional coactivator CRTC2

Abstract: Basic leucine zipper (bZip) transcription factors regulate cellular gene expression in response to a variety of extracellular signals and nutrient cues. Although the bZip domain is widely known to play significant roles in DNA binding and dimerization, recent studies point to an additional role for this motif in the recruitment of the transcriptional apparatus. For example, the cAMP response element binding protein (CREB)-regulated transcriptional coactivator (CRTC) family of transcriptional coactivators has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 42 publications
2
78
1
Order By: Relevance
“…In Vibrio cholerae, the wing region of the HTH of ToxR interacts with a second transcriptional regulator, TcpP, to activate gene expression (28), and in the marine bacterium Erythrobacter litoralis, interaction between the HTH domain and the light-oxygen-voltage domain of the blue-lightactivated photosensory protein (EL222) inhibits DNA binding (29). Other examples of DBD interactions have also been reported (26,27,30,31).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In Vibrio cholerae, the wing region of the HTH of ToxR interacts with a second transcriptional regulator, TcpP, to activate gene expression (28), and in the marine bacterium Erythrobacter litoralis, interaction between the HTH domain and the light-oxygen-voltage domain of the blue-lightactivated photosensory protein (EL222) inhibits DNA binding (29). Other examples of DBD interactions have also been reported (26,27,30,31).…”
Section: Resultsmentioning
confidence: 98%
“…There are several examples of DBDs interacting with other proteins (or domains), illustrating an important secondary function for DBDs, in addition to binding DNA (26)(27)(28)(29)(30)(31)(32). It is therefore no surprise that DBDs have evolved the ability to bind other proteins or other DBDs to gain additional functions, since many promoters contain DNA binding sites that are within a few base pairs of each other or even overlap.…”
mentioning
confidence: 99%
“…SEC-MALS experiments were performed and analyzed exactly as described previously (51). Proteins or protein mixtures of 37-100 ÎŒM in 20 mM Tris buffer (pH 7.4) containing 200 mM NaCl and 2 mM DTT or 50 mM Tris buffer (pH 8.0), 200 mM NaCl, and 2 mM tris(2-carboxyethyl)phosphine were used.…”
Section: Methodsmentioning
confidence: 99%
“…4B). Importantly, K33 is immediately adjacent to two residues conserved across all three CRTC family members that were recently shown to be important for interactions with the CREB bZip domain (45). The disabling effects of the K33P mutant on the native EVX1 promoter were confirmed using a completely defined 5×GAL4::UAS promoter, which revealed that the C1/M2 K33P mutant could not activate either CREB or its paralog ATF1 (Fig.…”
Section: Tetomentioning
confidence: 82%